CHALLENGES AND STRATEGIES FOR RECRUITING REPRESENTATIVE SAMPLES IN RESEARCH AND IMPLICATIONS FOR GENERALIZABILITY - Aliyu Abubakar, Suleiman; Musa Tafida, Abubakar; Shuaibu Umar, Shitu; Tijjani Usman, Ishaq; Ibrahim Joseph, Orume; Yusuf Agana, Kemi (African Journal of Social and Behavioural Sciences, 2024)
This paper examines the challenges in recruiting representative samples, the impact on generalizability, and practical strategies for improving recruitment in diverse populations. It starts by explaining the concept of representative samples and then explains the generalization of findings. The paper further defines recruiting of representative samples as a process whereby research employs a subset of the population in order to collect data so as to generalize the information gotten from the sample to the general population. The paper further explains the consequences of recruiting the samples. Also, it discusses the factors that influence generalization, importance of representative samples, it also explains the challenges in recruiting representative sample in research. Furthermore, the seminar looks at the approaches to mitigate challenges in recruiting representative samples which include; designed-based approaches, recruitment-based approaches, data collection approaches, analytical approaches and partnership-based approaches. Finally, the paper gave some recommendations for the best practices in recruiting representative samples and generalizability of findings.